What makes it so hard to look and to listen? Exploring the use of the Cognitive and Affective Supervisory Approach with children's social work managers. Issue 2 (3rd April 2018) - Turney, Danielle; Ruch, Gillian
ABSTRACT: This paper reports on the findings of an ESRC-funded Knowledge Exchange project designed to explore the contribution of an innovative approach to supervision to social work practitioners' assessment and decision-making practices. The Cognitive and Affective Supervisory Approach (CASA) is informed by cognitive interviewing techniques originally designed to elicit best evidence from witnesses and victims of crime. Adapted here for use in childcare social work supervision contexts, this model is designed to enhance the quantity and quality of information available for decision-making. Facilitating the reporting of both 'event information' and 'emotion information', it allows a more detailed picture to emerge of events, as recalled by the individual involved, and the meaning they give to them. Practice supervisors from Children's Services in two local authorities undertook to introduce the CASA into supervision sessions and were supported in this through the provision of regular reflective group discussions. The project findings highlight the challenges for practitioners of 'detailed looking' and for supervisors of 'active listening'. The paper concludes by acknowledging that the CASA's successful contribution to decision-making is contingent on both the motivation and confidence of supervisors to develop their skills and an organisational commitment to, and resourcing of, reflective supervisory practices and spaces.